Ovarian reserve in patients who have undergone endometriosis surgery - Džatić Smiljković, Olivera; Vasiljević, Mladenko; Rudić, Ivana; Vugdelić, Jelena; Ristić, Aleksandar; Vugdelić, Rada (Vojnosanitetski pregled, 2020)
Background/Aim. Endometriosis is a gynaecological disorder characterized by the presence of endometrial tissue outside the uterine cavity. The aim of this paper was to determine the effect of laparoscopic cystotomy and cystectomy on ovarian function, as well as to compare these two methods in terms of qualitative and quantitative damage to the ovaries, achieved pregnancies and recurrence. Methods. The prospective study, conducted in “Narodni Front” Obstetrics and Gynaecology Clinic in Belgrade at the Endoscopic Infertility Treatment Ward, included a total of 150 patients. The study group was represented by 100 patients who underwent a surgical treatment of endometrial ovarian cysts. The patients in the study group were divided into 2 subgroups: Subgroup I consisted of 50 patients who underwent a laparoscopic cystotomy (incision of the cyst and thermal coagulation) and subgroup II which included 50 women who underwent a laparoscopic cystectomy. The control group consised of patients who underwent a surgery due to tubal factor infertility. The following parameters of the ovarian function were tested: the ovarian volume, the antral follicle count, the presence of the preovulatory follicle on the operated ovary, the serum levels of anti-Müllerian hormone (AMH), follicle-stimulating hormone (FSH), ovarian tumor marker (Ca 125), inhibin B, as well as the rate of achieved pregnancies one year after the surgery. Results. The ovarian volume and the antral follicle count as well as the FSH values were significantly higher in the control group in comparison with the patients in the study group. There were no significant differences in the ovarian volume, the antral follicle count, the AMH values and inhibin B values in the study group between the patients with cystectomy and those with the incision and coagulation of the cyst. Conclusion. Both surgical techniques diminished the ovarian reserve: cystectomy was more aggressive method in terms of the damage inflicted on the ovarian tissue, and incision with coagulation carried a higher risk of recurrence.
Keywords: endometriosis; infertility; laparoscopy; cystectomy; cystotomy; treatment outcome.